On The Stability Problem of Quadratic Functional Equations in 2-Banach Spaces (JOURNAL OF ADVANCES IN PHYSICS, 2017)
In this paper, we investigate the stability problem in the spirit of Hyers-Ulam, Rassias and Gavruta for the quadratic functional equation: f(2x + y) + f(2x - y) = 2f(x + y) + 2f(x - y) + 4f(x) - 2f(y) in 2-Banach spaces. These results extend the generalized Hyers-Ulam stability results by the quadratic functional equation in normed spaces to 2-Banach spaces.